Global geographic distribution and host range of fusarium circinatum, the causal agent of pine pitch canker - Drenkhan, Rein; Ganley, Beccy; Martín-García, Jorge; Vahalík, Petr; Adamson, Kalev; Adamčíková, Katarína; Ahumada, Rodrigo; Blank, Lior; Bragança, Helena; Capretti, Paolo; Cleary, Michelle R.; Cornejo, Carolina; et al. (My University, 2020)
Fusarium circinatum, the causal agent of pine pitch canker (PPC), is currently one of the most important threats of Pinus spp. globally. This pathogen is known in many pine-growing regions, including natural and planted forests, and can affect all life stages of trees, from emerging seedlings to mature trees. Despite the importance of PPC, the global distribution of F. circinatum is poorly documented, and this problem is also true of the hosts within countries that are affected. The aim of this study was to review the global distribution of F. circinatum, with a particular focus on Europe. We considered (1) the current and historical pathogen records, both positive and negative, based on confirmed reports from Europe and globally; (2) the genetic diversity and population structure of the pathogen; (3) the current distribution of PPC in Europe, comparing published models of predicted disease distribution; and (4) host susceptibility by reviewing literature and generating a comprehensive list of known hosts for the fungus. These data were collated from 41 countries and used to compile a specially constructed geo-database. A review of 6297 observation records showed that F. circinatum and the symptoms it causes on conifers occurred in 14 countries, including four in Europe, and is absent in 28 countries. Field observations and experimental data from 138 host species revealed 106 susceptible host species including 85 Pinus species, 6 non-pine tree species and 15 grass and herb species. Our data confirm that susceptibility to F. circinatum varies between different host species, tree ages and environmental characteristics. Knowledge on the geographic distribution, host range and the relative susceptibility of different hosts is essential for disease management, mitigation and containment strategies. The findings reported in this review will support countries that are currently free of F. circinatum in implementing effective procedures and restrictions and prevent further spread of the pathogen.
Keywords: Climate change; Interactive map of pathogen; Invasive pathogen; Susceptibility